Politik Keamanan Siber dalam Membangun Kedaulatan Siber di Indonesia Melalui Penguatan Peran Badan Siber dan Sandi Negara - Muhammad Prakoso Aji (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
In an increasingly interconnected digital world, cybersecurity has emerged as a crucial element of national resilience and global political competition. The growing frequency of cyberattacks and data breaches underscores the urgency for Indonesia to strengthen its institutional capacity in securing cyberspace and protecting national sovereignty. In this context, cybersecurity politics determine how state institutions negotiate authority, coordinate policies, and mobilize resources to build digital resilience. This study analyzes the dynamics of cybersecurity politics and their influence on Indonesia’s efforts to achieve cyber sovereignty through the strengthening of the National Cyber and Crypto Agency (BSSN). Using a qualitative descriptive approach supported by literature review and policy analysis, the study applies the theory of state sovereignty and the framework of cybersecurity political factors. Findings reveal that BSSN plays a pivotal role as the state’s representative in maintaining cyber sovereignty amid complex inter-agency coordination, overlapping mandates, and regulatory uncertainty. Political, technological, and institutional factors significantly shape Indonesia’s cybersecurity governance, influencing how the state responds to both domestic vulnerabilities and international cyber threats. Nevertheless, the persistence of sectoral ego, fragmented authority, and the absence of a comprehensive Cyber Security and Resilience Law continue to hinder policy integration and weaken institutional effectiveness. The study concludes that strengthening BSSN’s authority, through legal ratification, increased budgetary support, organizational reform, and enhanced cyber diplomacy, is essential to establish an integrated and adaptive national cybersecurity system capable of safeguarding Indonesia’s sovereignty in cyberspace while aligning with global best practices in cyber governance.